Orthostatic hypotension predicts all-cause mortality and coronary events in middle-aged individuals (The Malmö Preventive Project) - Fedorowski, Artur (Oxford University Press, 2010)
AIMS: Orthostatic hypotension (OH) has been linked to increased mortality and incidence of cardiovascular disease in various risk groups, but determinants and consequences of OH in the general population are poorly studied. METHODS AND RESULTS: Prospective data of the Swedish ‘Malmö Preventive Project’ (n = 33 346, 67.3% men, mean age 45.7 ± 7.4 years, mean follow-up 22.7 ± 6.0 years) were analysed. Orthostatic hypotension was found in 6.2% of study participants and was associated with age, female gender, hypertension, antihypertensive treatment, increased heart rate, diabetes, low BMI, and current smoking. In Cox regression analysis, individuals with OH had significantly increased all-cause mortality (in particular those aged less than 42 years) and coronary event (CE) risk. Mortality and CE risk were distinctly higher in those with systolic blood pressure (BP) fall ≥30 mmHg [hazard ratio (HR): 1.6, 95% CI 1.3–1.9, P < 0.0001 and 1.6, 95% CI 1.2–2.1, P = 0.001] and diastolic BP fall ≥15 mmHg (HR: 1.4, 95% CI 1.1–1.9, P = 0.024 and 1.7, 95% CI 1.1–2.5, P = 0.01). In addition, impaired diastolic BP response had relatively greater impact (per mmHg) on CE incidence than systolic reaction. CONCLUSION: Orthostatic hypotension can be detected in ∼6% of middle-aged individuals and is often associated with such comorbidities as hypertension or diabetes. Presence of OH increases mortality and CE risk, independently of traditional risk factors. Although both impaired systolic and diastolic responses predict adverse events, the diastolic impairment shows stronger association with coronary disease.